Prosthesis Mapping and Forecasting as a Direction of Innovation in Prosthesis Product Development - Isnaini Nurisusilawati; Muhammad Yusro (OPSI, 2021)
The objective of this study is to make a need assessment in the form of identifying trends in the need for prostheses and mapping the priority types of prostheses developed at Dr. R. Soeharso Orthopedic Public Hospital, Surakarta as a reference for innovation in the development of prosthesis products at Dr. R. Soeharso Orthopedic Public Hospital, Surakarta. The method used was descriptive analysis and moving average forecasting of historical data on the use of prostheses. From the results of the descriptive analysis, it was found that the most common types of the prosthesis were under the knee prostheses and the types of prostheses that mostly used imported components were finger prostheses and prostheses that have been developed locally which were lower and upper knee prostheses and also Syme. The results of the prediction of the number of prostheses showed a stable trend and tended to increase slightly with the MAD error rate of 2.375 and MSE of 10.378 and MAPE of 36%. With this accuracy, the results of the forecasting can be used as a reference for the hospital to make supplies of prosthesis components in the next period so that the time for making prostheses can be shortened. Meanwhile, for the development of the direction of innovation, recommendations for the type of prosthesis that is a priority to be developed at Dr. R. Soeharso Orthopedic Public Hospital, Surakarta is an innovation of under-knee and finger prostheses by implementing low-cost product designs.